PENGUATAN PERAN POKDARWIS DAN UKM UNTUK PENGEMBANGAN PELAGA AGROTOURISM PARK BERBASIS MASYARAKAT - I Wayan Pantiyasa; Moh Agus Sutiarso; I Nyoman Arto Suprapto (Share : Journal of Service Learning, 2021)
The goal of community service in the second year (2020) in Pelaga village is to increase the role of tourism aware groups (Pokdarwis) and small business groups (SMEs) for the development of Pelaga Agrotourism Park-based on community. Through mentoring done by the team has been successfully created preferred tour packages and promotional tools online on Youtube, Facebook and Instagram. Agricultural products as supporting tourism produced by SME groups have been successfully improved quality and performance by using the brand Pelaga Agrotourism Park. It is hoped that the use of destination branding will increase the promotion and marketing of agribusiness products and Pelaga village as an agrotourism destination. Keywords: Pelaga Agrotourism Park, village community empowerment.